Extended spectrum β-lactamase producing Shigella flexneri serotype-2 causing bacteremia in a patient with uncontrolled diabetes mellitus - Marilyn M Ninan; Tarun K George; V Balaji; I Ramya (Wolters Kluwer Medknow Publications, 2016)
We report a case of Shigella flexneri serotype-2 causing bacteremia in an elderly gentleman with uncontrolled diabetes mellitus, who had no other apparent risk factors. Antibiotic susceptibility testing revealed that the organism was a multidrug resistant extended spectrum beta-lactamase producing straian, which was confirmed by molecular characterization. This rare case alerts both the clinician and microbiologist to a previously unaddressed risk factor of Shigella spp. causing bacteremia, as well as emerging resistant strains that are on the rise in immunocompromised patients.